P574 Rectal and pharyngeal M. genitalium among Men who have Sex with Men (MSM): results from a longitudinal cohort study. (14th July 2019) - Barbee, Lindley; Golden, Matthew; Soge, Olusegun; Haglund, Micaela; Yeung, Winnie; Khosropour, Christine; Hughes, James; Manhart, Lisa
Abstract : Background: Little is known about the natural history of rectal and pharyngeal Mycoplasma genitalium (MG). Methods: From March 2016 to December 2018, we enrolled 140 high-risk MSM in a 12-month cohort study. Eligibility criteria included: age ≥18 years, report of receptive anal intercourse, and ≥ 1 of the following in ≤12 months: (1) gonorrhea, chlamydia or syphilis; (2) methamphetamine or popper use, or (3) ≥2 sex partners in ≤2 months or ≥5 in ≤12 months. Each week, men collected pharyngeal and rectal swabs and completed an electronic sex diary. We tested swabs for MG (Aptima, Hologic, Inc.) at study completion. Infection was defined as ≥ 2 consecutive positive tests; clearance was ≥ 2 consecutively negative tests. We calculated person-weeks-at-risk to estimate incidence and used Kaplan Meier curves to estimate duration of infection. We censored subjects who had a positive swab in the final study week, received doxycycline or azithromycin and obtained clearance in the following 3 weeks, or were lost-to-follow-up. None received moxifloxacin. Results: At week 1, the prevalence of rectal and pharyngeal MG was 8% (4/48) and 2% (1/48), respectively. Among 48 men with results from 3, 579 specimens, 12 (25%) had ≥1 rectal, and 5 (10%) had ≥1 pharyngeal MG infection. In 1, 504 person-weeks-at-risk, rectal MG incidence was 38 (95%CI: 19–68) infections per 100 person-years. In 1, 715 person-weeks-at-risk, pharyngeal MG incidence was 15 (95%CI: 5–35) per 100 person-years. Forty percent (6/15) of rectal and 50% (3/6) of pharyngeal infections were censored. Rectal and pharyngeal infections had estimated median durations of 30 (95%CI: 6 – undefined) and 16 (95%CI: 3 – undefined) weeks, respectively. Blips, single positive tests that did not meet criteria for infection, occurred in 8 (17%) men with 17 rectal and 4 (8%) men with 10 pharyngeal MG-positive tests. Conclusion xtragenital, MG, including pharyngeal infection, is common and persistent among high-risk MSM. Disclosure: No significant relationships.